A study of haptic effects in endovascular interventions - Harun @ Ramli, Hafiz Rashidi; Ako, Emmanul; Saripan, M. Iqbal; Bello, Fernando (Faculty of Manufacturing and Mechatronic Engineering Technology Universiti Malaysia Pahang, 2021)
During an endovascular intervention, interventionists rely on their sense of touch to perform the procedures correctly. However, there is a paucity of literature regarding the intricacies of the haptic component of the interventions. The objectives of this study were to capture the types and magnitude of haptic effects during real-life interventions from subject matter experts. The study consisted of an online questionnaire and a force measurement experiment to help determine the force types and magnitude. Participants were interventionists with significant procedural experience. The data recorded from the online questionnaire and the experimental study was analysed using descriptive statistics and hypothesis testing techniques. Participants identified four different types of haptic effects: translational resistance, rotational resistance, bump effect and heart beat pressure effect. The characteristics of each effect, such as factor of occurrence and direction, were established and they were compared against each other. Translational resistance was recognised as the strongest, followed by rotational resistance, bump effect and heart beat pressure. In the force measurement experiment, the forces involved in the generation of translational resistance were found to be in the range 0-0.5 N in healthy vessels, 0.5 – 1.5 N in tortuous/narrowed vessels and 1.5 – 2 N in calcified or occluded vessels. Measurements for the bump effect provided less conclusive results due to its subtle nature, although current findings suggest forces between 0.1 – 0.2 N. Overall, the study was successful in expanding current knowledge of haptic effects in endovascular interventions, highlighting the existence of a variety of effects and their characteristics.